1972
DOI: 10.6028/nbs.ir.73-129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GRP rod and rope materials and associated end fittings

Abstract: An extensive and varied test program was carried out on four GRP rod and rope materials to evaluate tensile strengths, moduli of elasticity, flexibility at low temperatures, effects of simulated Aeolian vibration, and stress-rupture properties at moderate elevated temperatures both with and without high humidity. The effects of elevated temperature on long-term storage capabilities were investigated, and diametertemperature relationships were established for avoiding buckling due to storage in a coiled conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…Differences between the original free lengths of specimens of different styles reflect differences in the lengths of their end fittings, since all of the specimens were manufactured to have the same approximate length between the clevis pins on their end fittings. 4.…”
Section: Preliminary Tensile Testslmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences between the original free lengths of specimens of different styles reflect differences in the lengths of their end fittings, since all of the specimens were manufactured to have the same approximate length between the clevis pins on their end fittings. 4.…”
Section: Preliminary Tensile Testslmentioning
confidence: 99%
“…While the potting compound exhibited the flexibility, under normal environmental conditions, that NBS work has shown to be desirable [4], its degradation under the simulated weathering exposures was excessive.…”
Section: End Fittingsmentioning
confidence: 99%
See 2 more Smart Citations
“…If tensile strengths of the materials are to provide a meaningful measure of product improvement, it is necessary to determine the tensile strengths accurately. However, previous work in this laboratory [1,2] has shown that the end fittings for these materials, which are available commercially, are not generally capable of withstanding the tensile forces which are required to fracture these materials in a true tensile mode. Hence, there has been a need, first, to develop end fittings, for use in the laboratory, which can gen-' erate the full tensile strengths of the materials.…”
Section: Scopementioning
confidence: 99%